English Deutsch Français Italiano Español Português 繁體中文 Bahasa Indonesia Tiếng Việt ภาษาไทย
All categories

3x-6y=6
9x-3y=8

2/3x-1/2y=3
1/3x-1/4y=3/2

4x+4y=5
2x-8y=-5

2007-02-02 05:43:35 · 4 answers · asked by Jules 4 in Science & Mathematics Mathematics

4 answers

1. (1)*-3
-9x+18y=-18
9x-3y=8
adding
15y--10
y=-2/3
sub
x=2/3

2.2/3x-1/2y=3
-2/3x+1/2y=-3/4
no solution

3.4x+4y=5
-4x+16y=10
adding
20y=15
y=3/4
sub
4x+3=5
4x=2
x=1/2

2007-02-02 05:49:27 · answer #1 · answered by raj 7 · 1 0

1)
you should multiply the lower eq. by -2 so you get
3x-6y=6
-18x+6y=-16
thus, by addition, of the equations you get
-15x=-10
x=10/15
then substitute x in any initian equation and solve for y and there you go

2) Its the same path, multiply the lower equation by -2
thus, you get
2/3x-1/2y=3
-2/3x+1/2y=-3
this one, when you add the equations, you get
0=0 so you can't solve it 'cause both equations are the same

3) Here, you multiply the first eq. by 2
8x+8y=10
2x-8y=-5
adding them you get..
10x=5
and x=5/10=1/2
substitute x in any initial equation and solve for y

2007-02-02 06:27:49 · answer #2 · answered by IQ DOSON 2 · 0 0

1. 12x-3y=14

2. x-(1/4)y= -3/2

3. 6x-4y=10

2007-02-02 05:55:05 · answer #3 · answered by sexylebanesegirl 1 · 0 0

Multiply it by way of '-2'. 3x - y = 3 ---> Multiply by way of '-2' -2x + 2y = 6 -6x + 2y = -6 -2x + 2y = 6 ------------------ Subtract -4x = -12 x = 3. replace this 'x' cost in the two of the unique equations to get the 'y' cost. Edit : you won't multiply by way of 3. You 'replace'. 3x - y = 3 ---> replace the cost of 'x'. 3(3) - y = 3 9 - 3 = y ---> y = 6 So answer is 6.(0.33 determination)

2016-12-13 07:12:24 · answer #4 · answered by goslin 4 · 0 0

fedest.com, questions and answers